Theology of Science as an Intertextual Reading: The Bible, the Book of Nature, and Narrative Paradigm - Sierotowicz, Tadeusz (2024)
The paper addresses the question of the identity of theology of science, fostering its interpretation as an intertextual narration. The starting point is the consideration of the domain of theology of science, which is viewed as a third domain of truth, according to Hans Urs von Balthasar. An analysis of the Swiss theologian’s perspective on this subject and the concept of God’s unknowability presents a strong counterargument to the claim that the natural sciences serve as a locus theologicus. Theology of science, nonetheless, exists and is engaged in a lively dialogue between science and theology, encompassing both the Revelation of God and the natural world or the Bible and the Book of Nature. What kind of discourse is this? This question concerns the position of theology of science within the field of science, specifically its objectivity and rigour, according to Evandro Agazzi’s analogical notion of science. Both the Bible and the Book of Nature ensure the objectivity of theology of science, while its rigour is established by the narrative paradigm. Therefore, theology of science can be seen as an intertextual narrative that engages both the Bible and the Book of Nature. The narrative paradigm of theology of science is subsequently elucidated, with particular emphasis on its cognitive aspects, narrative reasoning, the corresponding verification method, and Jewish corrective. The conclusion outlines a special task for theology of science in the modern age.
Keywords: Evandro Agazzi; Hans Urs Von Balthasar; Midrash; the narrative paradigm; locus theologicus; domain and rigour of theology of science